Financing Strategy to Execute Business Opportunity in Supplying Building Material in Real Estate - Adhyaksa, Muhamad Reynaldi (Journal of World Science, 2022)
Concerns about distribution and supplier quality are common among developer business owners. In the future, the cost of material transportation could prevent housing developer business owners from making a decision, not to mention the risk of goods availability when housing demand is high, or housing developers lose money when housing demand is high. Delivery damage. Adhyaksa Precast may be the answer, but before establishing a business, the founder must conduct analysis. Before starting, especially in the financial industry, the founder must determine the firm's long-term viability. The initiator must consider what will benefit and hurt his company. This research uses Minitab to predict home sales. A feasibility study is used to properly run the business. The margin between cooperating and not cooperating is small, and the business will last three years. 1. The company's finances. Bank loan plus own equity is the best funding option so far. 2. There is a large potential for income and profit if CV Satria Yaksa Mandiri and its clients can reach a commercial agreement soon. 3. The firm determined that a combination of bank loan and own equity could cover the entire investment (Rp.1.046.000.000). All bank loan feasibilities are positive (IRR, NPV, PI, ROI, PP, US Index, and PP). 5. With the lower price, cooperative business financial calculations are lower. The corporation prefers the cooperative relationship because it has more free cash flow (the rent fee is free).